KEPEMIMPINAN INKLUSIF KEPALA SEKOLAH DALAM MENGEMBANGKAN BUDAYA SEKOLAH YANG RESPONSIF TERHADAP KEBERAGAMAN - Johan Wahyu Tri Astuti; Elfani Hunafa Salsabella (STKIP Pesisir Selatan, 2026)
A school culture that is responsive to diversity is one of the key elements in creating a conducive educational environment for all school residents. The diversity in question includes cultural, religious, socio-economic, language, gender, and special needs of teachers and students. However, in reality, there are still a number of schools that are not fully able to accommodate and respond optimally to this diversity, both in policies, learning practices, and social interaction in the school environment. In addition, previous studies have not extensively reviewed the role of inclusive leadership of school principals in building a school culture that is responsive to diversity in a systematic and sustainable manner, so there are still research gaps that need to be studied and answered through further research. This study aims to describe the role of inclusive leadership of school principals in the formation and management of a school culture that is responsive to diversity. This study uses a literature review method by examining a wide range of literature related to inclusive leadership of principals, and a school culture that is responsive to diversity. The results of this study show that inclusive leadership of school principals has an important role in shaping and managing a school culture that is responsive to diversity so that all school residents feel valued, accepted, and have equal opportunities in the educational process.